2004
DOI: 10.1088/0264-9381/21/4/016
|View full text |Cite
|
Sign up to set email alerts
|

Magnetized orbits around a Kerr black hole

Abstract: We study the motion of magnetized particles near a rotating black hole. The main result is that the spacetime curvature and electromagnetic field conspire to allow for the existence, inside the ergosphere, of stable circular orbits occupied by particles with negative total energy and angular momentum. Since these particles would never populate stable orbits were they not magnetized, a large binding energy is required to let them exist. A simple model of a magnetized belt in the ergosphere of a massive black ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 8 publications
0
38
0
Order By: Relevance
“…In the limiting case when γ = 1 we will get the expression (16) for the magnetized particle motion around Schwarzschild BH in the magnetic field (see, e.g., [73]). Consider the conditionṡ…”
Section: Magnetized Particles Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the limiting case when γ = 1 we will get the expression (16) for the magnetized particle motion around Schwarzschild BH in the magnetic field (see, e.g., [73]). Consider the conditionṡ…”
Section: Magnetized Particles Motionmentioning
confidence: 99%
“…The formalism of studying the motion of particles with a nonzero magnetic dipole moment around weakly magnetized Schwarzschild BH was first proposed in Reference [72]. This study has been extended to the rotating Kerr BH case in [73]. The magnetized particle dynamics around BH in alternate theories of gravity have been studied by several authors [50,[74][75][76][77][78][79][80][81].…”
Section: Introductionmentioning
confidence: 99%
“…(4.5) we can also discuss the motion of a magnetic dipole [21,22,6,7] with magnetic moment µ α = −(µ/r)δ α θ . The force driving the motion in this case is given by…”
Section: Particles With a Magnetic Dipole Momentmentioning
confidence: 99%
“…It was also shown that magnetized particles can move along stable non-geodesic, spatially circular equatorial orbits with the radius smaller than innermost stable circular orbits (ISCO) (in the case of non-rotating black holes) and close to photon orbit. The magnetized particle motion around rotating black holes has been studied in [43].…”
Section: Introductionmentioning
confidence: 99%